2019
DOI: 10.1186/s12889-019-7317-9
|View full text |Cite
|
Sign up to set email alerts
|

Low to medium-low risk perception for dengue, chikungunya and Zika outbreaks by infectious diseases physicians in France, Western Europe

Abstract: BackgroundMany tropical countries are currently experiencing dengue (DEN), chikungunya (CHIK) and also more recently Zika (ZIKA) epidemics (particularly in Latin America). Although the risk of transmission and spread of these infections in temperate regions remains a controversial issue, vector-borne diseases have been widely reported in the media and have been the focus of preventive strategies by national and international policy-makers and public health authorities. In this context, we wanted to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…However, the same study suggested that an earlier outbreak detection by just two generations of transmission (about 3 weeks) could have reduced the number of cases occurring after outbreak detection by over two thirds, therefore stressing the importance of a surveillance system capable of quickly detecting the introduction of tropical arboviruses, as also observed in France where anticipating vector control intervention by 10 days would have reduced the final outbreak size by 30–40% fewer cases [ 25 , 32 ]. This may be achieved, at least for chikungunya and other non-endemic diseases, by means of preventive rather than reactive measures such as strengthening surveillance of imported cases, raising awareness in both travelers and general practitioners [ 13 , 33 ] and an integrated management of vector population [ 31 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the same study suggested that an earlier outbreak detection by just two generations of transmission (about 3 weeks) could have reduced the number of cases occurring after outbreak detection by over two thirds, therefore stressing the importance of a surveillance system capable of quickly detecting the introduction of tropical arboviruses, as also observed in France where anticipating vector control intervention by 10 days would have reduced the final outbreak size by 30–40% fewer cases [ 25 , 32 ]. This may be achieved, at least for chikungunya and other non-endemic diseases, by means of preventive rather than reactive measures such as strengthening surveillance of imported cases, raising awareness in both travelers and general practitioners [ 13 , 33 ] and an integrated management of vector population [ 31 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that gardeners’ community and, to a larger extent, French urban citizens are not prepared to face a potential arbovirus outbreak. Despite the expansion of arboviral diseases in France and on a larger scale in Europe, the European population does not perceive the risk of transmission of these viruses by mosquitoes as a serious problem for the future [ 35 , 40 , 46 ]. Educating people on the dual threat mosquitoes pose in terms biting and disease transmission could have broad implications due to their immediate impact through deterioration of quality of life by bites and the future consequences by proliferation of mosquito-borne diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding rare CD, health professionals often lack the necessary skills to correctly identify and treat unfamiliar pathologies, due to their low prevalence in the countries where they are working or because they are newly emerging diseases [14]. In the same way, the increase in global mobility for tourism or trade poses similar risks of rare diseases in travellers, often implying a particular challenge for diagnosis and management [11].…”
Section: Introductionmentioning
confidence: 99%